Gothic Invasions : imperialism, war and fin-de-siècle popular fiction - Bulfin, Ailise (Gothic literary studies., 2018)
Gothic Invasions investigates the prevalent concern with invasion and war in fin-de-siècle British popular fiction, identifies the role of imperial expansion in generating fears of invasion, and explores how these fears were expressed transgenerically in narratives of invasion drawing strongly upon the conventions and themes of gothic writing.